Theory of Ultralong‐Range Rydberg Molecule Formation Incorporating Spin‐Dependent Relativistic Effects: Cs(6s)–Cs(np) as Case Study. Issue 22 (31st October 2016) - Markson, Samuel; Rittenhouse, Seth T.; Schmidt, Richard; Shaffer, James P.; Sadeghpour, H. R.
Abstract: We calculate vibrational spectra of ultralong‐range Cs(32p) Rydberg molecules that form in an ultracold gas of Cs atoms. We account for the partial‐wave scattering of the Rydberg electrons from the Cs perturber atoms by including the full set of spin‐resolved 1, 3 SJ and 1, 3 PJ scattering phase shifts, and allow for the mixing of singlet ( S= 0) and triplet ( S= 1) spin states through Rydberg electron spin‐orbit and ground state electron hyperfine interactions. Excellent agreement with observed data in Saßmannshausen et al. [ Phys. Rev. Lett . 2015, 113, 133201] in line positions and profiles is obtained. We also determine the spin‐dependent permanent electric dipole moments for these molecules. This is the first such calculation of ultralong‐range Rydberg molecules for which all of the relativistic contributions are accounted. Abstract : Relatively cold : The vibrational spectra of ultralong‐range Cs(32p) Rydberg molecules that form in an ultracold gas of Cs atoms are calculated. This is the first such calculation of ultralong‐range Rydberg molecules for which all of the relativistic contributions are accounted.